Prevalence of depression, syndemic factors and their impact on viral suppression among female sex workers living with HIV in eThekwini, South Africa - Anvita Bhardwaj; Carly A. Comins; Vijay Guddera; Mfezi Mcingana; Katherine Young; Rene Phetlhu; Ntambue Mulumba; Sharmistha Mishra; Harry Hausler; Stefan Baral; Sheree Schwartz (BMC, 2023)
Abstract Introduction Over half of female sex workers (FSW) in South Africa are living with HIV and clinical depression has been frequently documented among FSW. Data characterizing structural determinants of depression and the role of syndemic theory, synergistically interacting disease states, on viral suppression among FSW in South Africa are limited. Methods Between July 2018-March 2020, non-pregnant, cisgender women (≥ 18 years), reporting sex work as their primary income source, and diagnosed with HIV for ≥ 6 months were enrolled into the Siyaphambili trial in eThekwini, South Africa. Using baseline data, robust Poisson regression models were used to assess correlates of depression and associations between depression and syndemic factors on viral suppression. Results Of 1,384 participants, 459 (33%) screened positive for depression, defined as a score of ≥ 10 on the PHQ-9. Physical and sexual violence, drug use, alcohol use, anticipated stigma and internalized stigma were univariately associated with depression (all p's < 0.05) and included the multivariate model. In the multivariate regression, prevalence of depression was higher among participants experiencing sexual violence (PR = 1.47 95% CI:1.24,1.73), physical violence 5 times or more in < 6 months (PR = 1.38 95% CI:1.07, 1.80), using illicit drugs in the last month (PR = 1.23 95%:CI 1.04, 1.48), and reporting higher levels of internalized stigma (PR = 1.11, 95% CI:1.04,1.18). Depression in the absence of the Substance Abuse, Violence and AIDS SAVA syndemic factors was associated with increased prevalence of unsuppressed viral load (aPR 1.24; 95% CI:1.08,1.43), and the SAVA substance use and violence syndemic was associated with an increase in unsuppressed viral load among non-depressed FSW (aPR 1.13; 95% CI:1.01, 1.26). Compared to those experiencing neither factors, those jointly experiencing depression and the SAVA syndemics were at increased risk for unsuppressed viral load (aPR 1.15; 95% CI:1.02,1.28). Conclusion Substance use, violence, and stigma were all associated with depression. Depression and syndemic factors (substance use + violence) were related to unsuppressed viral load; we did not observe higher unsuppressed viral load amongst those experiencing both depression and syndemic factors. Our findings point to the need to understand the unmet mental health needs of FSW living with HIV. Trial registration Clinical Trial Number: NCT03500172.